Peran Perempuan dalam Membangun UMKM di Kota Tanjungpinang - Indah Juwairiyah; Muhammad Andrianto; Rahma Syafitri (LPPM Universitas Terbuka, 2022)
Industry as one of the development strategies that is considered capable of advancing the growth process of a country. If a country has reached the industrial sector stage, the country is considered to have experienced the industrialization stage. Based on data obtained by the Department of Trade and Industry of Tanjungpinang City, the number of SMEs in 2022 to date is 925 SMEs. This study aims to determine the role of women in SMEs in Tanjungpinang City. This study uses a qualitative method by observing and collecting data obtained during an internship at the Department of Trade and Industry of Tanjungpinang City. Based on the results of the study, women SMEs in Tanjungpinang have an important role in the development of SMEs and the role of women in SMEs can help the family economy and can even help the national economy.